Trottoir : les multiples facettes d’un espace public de loisirs. Le cas de Mexico - Guénola Capron; Jérôme Monnet (EchoGéo)
In this article we expose the variety of spatial forms and social representations under which numerous types of leisure activities are deployed on the sidewalks in the Mexico City metropolitan area. In this context of important socio-spatial inequalities and where the development of this public space, which is part of the roadway network, remains dominated, except in exceptional cases, by the functional imperative and the public order of traffic, we raise the question of the legitimacy of the different types of users to occupy it. We build upon the results of a collective research that we coordinated on the social and material production of sidewalks in Mexico City, and from this analysis we draw some orientations for policies that are more adapted to taking into account the uses and demands of city dwellers.